The Effect of Training and Compensation on Employee Performance through Job Satisfaction as a Mediation Variable in Minimarkets in Cirebon City - Putri, Icha Revika; Syarif Hidayat, Agi (Syntax Corporation, 2026)
This study aims to examine the effect of training and compensation on employee performance with job satisfaction as a mediating variable in the modern retail sector, especially minimarkets in Cirebon City. The study used an associative quantitative approach through a survey of 120 employees of Alfamart and Indomaret minimarkets. Data collection was carried out by questionnaire and analyzed using the PLS-SEM approach. The results of the study show that training and compensation have a positive effect on job satisfaction and employee performance. Job satisfaction has also been shown to play a role in improving employee performance and partially mediating the relationship between training and compensation to employee performance. These findings confirm that the provision of effective training and a fair compensation system can create a positive reciprocal relationship between companies and employees, as described in Social Exchange Theory. This research makes an empirical contribution to the development of human resource management studies in the modern retail sector and serves as a reference for practitioners in designing training and compensation policies oriented towards improving employee satisfaction and performance.